Community Based Tourism in Promoting Local Products for Cultural Preservation: A Case Study of Biji Ketapang Products at MSMEs Dapur Emil in Setu Babakan Betawi Cultural Village - Pradini, Gagih; Hendratono, Tonny; Priyanto, Sony Heru; Rahmawati, Ema; Trianto, Rachmad Rizky (International Journal of Education, Information Technology, and Others, 2025)
Community based tourism is an approach that involves the active participation of local communities in developing the potential of their region. This approach aims not only to improve economic wellbeing but also to play a significant role in preserving local culture. This study aims to examine the role of community-based tourism in promoting local products as an effort to preserve cultural heritage, with a case study on the traditional Betawi snack biji ketapang produced by MSMEs Dapur Emil in the Setu Babakan area. Biji ketapang, as one of the iconic Betawi foods, holds important cultural and historical value but is increasingly marginalized by modernization. This research uses a qualitative approach with data collection techniques including observation, interviews, and documentation. The findings indicate that community involvement in tourism activities particularly through the promotion and enhancement of local products can increase cultural awareness while providing economic value to local residents. MSMEs Dapur Emil acts as a key driver in preserving traditional culinary heritage and introducing Betawi cultural values to tourists. Therefore, the development of local products through communitybased tourism serves as an effective strategy for safeguarding cultural heritage and encouraging sustainable growth of local MSMEs.